The Effect of Group Guidance Services Using Experiential Learning Method on Students' Interpersonal Communication Skills: Group Guidance Services, Experiential Learning Method, Students' Interpersonal Communication Skills - Rahmawati, Endah; Astuti, Anita Dewi; Nur Aini, Novi; Dwi Mulyani, Nur Sya'ban Ratri (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to determine the Effect of Group Guidance Services with the Experiential Learning Method on Students' Interpersonal Communication Skills. The study is an experimental study. The design used is a Quasi experimental design with the type of Non-equivalent Control Group Design. The sampling technique used in this study is purposive sampling. While the data collection technique used is the Likert scale of interpersonal communication. The results of the validity test of the Likert scale from 54 items contained 8 invalid items because r count <0.05 and the reliability test obtained a value of 0.924 which means it has high reliability. The data analysis technique used is the Wilcoxon Signed Ranks test. The results of the Wilcoxon Signed Ranks test obtained a t-count of 36.7 and a t-table of -2803 and an asymptotic sig. (2-tiled) value of 0.005 <0.05, this indicates that Ho is rejected and Ha is accepted. namely